Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae) - Chen, Zhi-Teng (Zootaxa, 2020)
A Neotype is designated for Microperla geei Chu, 1928. This species was recently collected from Tianmu Mountain, Hangzhou City, Zhejiang Province of southeastern China. The male, female, larva, and egg of M. geei are described and illustrated. Identity of the Microperla species described by Stark & Sivec (2000) is discussed. Egg morphology of M. qinlinga Chen, 2019 is also described and compared with congeners.